Perancangan Infografis Tentang Kesadaran Tertib Lalu Lintas di Kota Mataram - Qaolan Jadid Subardan; Sandi Justitia Putra; I Nyoman Yoga Sumadewa (Universitas Lancang Kuning, 2020)
The very high growth of vehicles in the City of Mataram is not matched by public awareness of the importance of a good and correct traffic order in accordance with applicable regulations. This problem is what makes traffic accidents occur every year and continue to grow. The need for appropriate and appropriate new media that is out of the box or unusual for the public. So through this dedication activity, the service team will create an infographic work by applying ambient media to be the right media to socialize orderly awareness in traffic by displaying data about traffic accidents in the previous year. This work uses a design thinking methodology. The conclusion is that this infographic work provides a memorable experience for road users and evokes feelings and moods for the target audience to feel comfortable and happy when interacting with the work of the infographic